Excel 2013 bible - Walkenbach, John. (Indianapolis, IN : Wiley, 2013)
Details Excel's updated features, and explains how to use the software to import and analyze data, build pivot tables, create macros, identify data trends and patterns, and generate charts and diagrams.
Includes index.
oif 12/06/15
Loan
Keywords: Electronic spreadsheets